2018
DOI: 10.5455/aim.2018.26.125-129
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Shear Bond Strength of Orthodontic Brackets Using Direct and Indirect Bonding Methods in Vitro and in Vivo

Abstract: Aim:Aim of article was to compare the shear bond strength of indirectly and directly bonded orthodontic brackets.Materials and methods:The experimental in vitro study included 60 maxillary and mandibular premolars. Teeth were mounted on cold-cure acrylic blocks for each tooth separately and divided into two groups: directly bonded brackets (30 teeth) and indirectly bonded brackets (30 teeth). Brackets (Discovery, Roth 0.022”, Dentaurum, Ispringen, Germany) were bonded using Transbond XT (3M Unitek, Monrovia, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
2
13
0
3
Order By: Relevance
“…No significant difference of bond failure rate was found between the direct and indirect bonding in the meta-analysis. This finding corroborated the idea of the in vivo part of a recent research [40] indicating that average survival rate for directly bonded brackets and indirectly bonded brackets was 98.6 and 98.3%, respectively, without significant difference. During the indirect bonding, it was often practically difficult to place a tray for multiple teeth correctly with a uniform and steady pressure on each tooth [41], which might result in uneven/excessive adhesives or low bonding strength [2, 18, 42].…”
Section: Discussionsupporting
confidence: 91%
“…No significant difference of bond failure rate was found between the direct and indirect bonding in the meta-analysis. This finding corroborated the idea of the in vivo part of a recent research [40] indicating that average survival rate for directly bonded brackets and indirectly bonded brackets was 98.6 and 98.3%, respectively, without significant difference. During the indirect bonding, it was often practically difficult to place a tray for multiple teeth correctly with a uniform and steady pressure on each tooth [41], which might result in uneven/excessive adhesives or low bonding strength [2, 18, 42].…”
Section: Discussionsupporting
confidence: 91%
“…Authors have reported this system is very effective in tensile and shear bond strength and failure rate, when compared to other adhesives (Shimizu et al 2012). In addition, Transbond XT™ presents similar behavior when used in direct or indirect bonding techniques, being able of reaching the same clinical efficiency when the indirect bonding technique is performed properly (Menini et al 2014;Tessore et al 2017;Demirovic et al 2018;Sharma et al 2018). The custom base adapts so closely to the tooth that it is only necessary to use a thin film of primer between the custom base resin and the etched enamel.…”
Section: Discussionmentioning
confidence: 99%
“…The high costs involved in this process, however, still do not allow its routine use among most orthodontists. Despite the availability of these proposed variations, the indirect procedure is not yet the gold standard, probably because of numerous procedural variables that must be controlled to obtain successful indirect bonding (Demirovic et al 2018). It is supported by the extra expenses and duration of laboratory phase, and sensitivity of the multiphase technique.…”
Section: Introductionmentioning
confidence: 99%
“…Results of SBS revealed no statistical and clinical differences between the values obtained in the direct and indirect techniques (Table 1) [3,5,[7][8][9]17]. Moreover, bonding failure rates, total chairside time and the number of visits were comparable [18]. However, when adhesive remnant index (ARI) was assessed in a different study, bonding failure in the indirect technique was most prevalent in the area between the bracket base and the tooth surface [16].…”
Section: Development Of Bonding Systemsmentioning
confidence: 96%
“…Results of SBS revealed no statistical and clinical differences between the values obtained in the direct and indirect techniques (Table 1) [3,5,[7][8][9]17]. Moreover, bonding failure rates, total chairside time and the number of visits were comparable [18]. However, when…”
Section: Development Of Bonding Systemsmentioning
confidence: 98%